Current evidence for the use of blood-flow restriction in resistance training - Madden, S. J. (Journal of Australian Strength and Conditioning, 2019)
Blood flow restriction training has been shown to be a safe and effective method for promoting strength and hypertrophic changes at low intensities of resistance training as a result of both mechanical and metabolic physiological stress.